Mitotic CDK1 and 4E-BP1 II: A single phosphomimetic mutation in 4E-BP1 induces glucose intolerance in mice - Cao, Simon; Jurczak, Michael J.; Shuda, Yoko; Sun, Rui; Shuda, Masahiro; Chang, Yuan; Moore, Patrick S. (PLOS ONE, 2023)
Cyclin-dependent kinase 1 (CDK1)/cyclin B1 phosphorylates many of the same substrates as mTORC1 (a key regulator of glucose metabolism), including the eukaryotic initiation factor 4E-binding protein 1 (4E-BP1). Only mitotic CDK1 phosphorylates 4E-BP1 at residue S82 in mice (S83 in humans), in addition to the common 4E-BP1 phospho-acceptor sites phosphorylated by both CDK1 and mTORC1. We examined glucose metabolism in mice having a single aspartate phosphomimetic amino acid knock in substitution at the 4E-BP1 serine 82 (4E-BP1S82D) mimicking constitutive CDK1 phosphorylation. Knock-in homozygous 4E-BP1S82D and 4E-BP1S82A C57Bl/6N mice were assessed for glucose tolerance testing (GTT) and metabolic cage analysis on regular and on high-fat chow diets. Gastrocnemius tissues from 4E-BP1S82D and WT mice were subject to Reverse Phase Protein Array analysis. Since the bone marrow is one of the few tissues typically having cycling cells that transit mitosis, reciprocal bone-marrow transplants were performed between male 4E-BP1S82D and WT mice, followed by metabolic assessment, to determine the role of actively cycling cells on glucose homeostasis. Homozygous knock-in 4E-BP1S82D mice showed glucose intolerance that was markedly accentuated with a diabetogenic high-fat diet (p = 0.004). In contrast, homozygous mice with the unphosphorylatable alanine substitution (4E-BP1S82A) had normal glucose tolerance. Protein profiling of lean muscle tissues, largely arrested in G0, did not show protein expression or signaling changes that could account for these results. Reciprocal bone-marrow transplantation between 4E-BP1S82D and wild-type littermates revealed a trend for wild-type mice with 4E-BP1S82D marrow engraftment on high-fat diets to become hyperglycemic after glucose challenge. 4E-BP1S82D is a single amino acid substitution that induces glucose intolerance in mice. These findings indicate that glucose metabolism may be regulated by CDK1 4E-BP1 phosphorylation independent from mTOR and point towards an unexpected role for cycling cells that transit mitosis in diabetic glucose control.